Purificação, caracterização e atividade antifúngica da Mm-POX, uma peroxidase do látex de Marsdenia megalantha (GOYDER; MORILLO, 1994) - Oliveira, Henrique Pinho (2013)
The peroxidases are present in all living organisms and constitute a group of multifunctional enzymes with several biotechnological applications. In this group, the class III plant peroxidases (POX) (EC 1.11.1.7) are enzymes well characterized, with involvement in lignification, suberization, auxin catabolism, wound healing and plant defense. These enzymes have been detected in different parts of the plant, including the latex. The aim of this work was the purification, characterization and antifungal activity evaluation of a peroxidase from Marsdenia megalantha latex, an endemic species of the Caatinga. The latex was collected from plant grown in Quixadá, Ceará, Brazil, diluted (1:2) in 0.05 M Tris-HCl containing 0.15 M NaCl, pH 8.0, and subjected to centrifugation and dialysis against water. The supernatant was applied to a DEAE-Cellulose matrix previously equilibrated with 0.05 M sodium acetate buffer, pH 5.2 and two protein fractions were obtained. Elution of the non retained proteins (FnRd) was achivied by the equilibrium buffer, whereas the bound proteins (FRd) were eluted with 0.2 M NaCl in the same buffer. FnRd was subjected to a chromatography on Superose 12 HR 10/30 column, yielding two protein fractions (S1 and S2). S1 was shown to be a pure protein with peroxidasic activity, apparent molecular mass of 60 kDa, pI 5.2 and identity with other POXs, being named of M. megalantha peroxidase (Mm-POX). Mm-POX follows the Michaelis-Menten kinetics, with high affinity for guaiacol and H2O2, elevated thermal stability (60 °C, 1 hour) and optimum pH around 6.0. The catalytic activity of Mm-POX was reduced in the presence of classic peroxidases inhibitors, including azide, DTT, EDTA and Na2S2O5 and also in high concentrations of Na+, Mn2+ and salicylic acid. On the other hand, Ca2+ and Mg2+, even at low concentrations, were able to enhance the enzymatic activity of Mm-POX. In addition, Mm-POX was able to inhibit the Fusarium oxysporum and F. solani conidia germination. This action is probably due to changes in the cell membrane as well as induction of oxidative stress. The results reveal that Mm-POX is a class III peroxidase, being the first enzyme isolated from M. megalantha species, with potential use in the control of plant disease caused by fungi, adding biotechnological value to this enzyme.